PERBANDINGAN HASIL PEMERIKSAAN HbA1C ANTARA SEBELUM DAN SESUDAH MENGIKUTI PROLANIS PADA PASIEN DIABETES MELITUS TIPE 2 DI LABORATORIUM KIMIA FARMA RADIO DALAM - Nuryana, Muhammad Insyirah Rizieq; Setiawan, Heru; Pasaribu, Merci Monica (Jurnal Fisioterapi dan Kesehatan Indonesia, 2024)
Type 2 Diabetes Mellitus (T2DM) is a chronic disease that can occur when the pancreas cannot produce enough insulin or the body's insulin production cannot be used effectively again. According to the Indonesian Ministry of Health's Research and Development data in 2019, DKI Jakarta Province was in the first position diagnosed with T2DM with a prevalence of 3.4% in 2018. Prolanis is a BPJS Health program that collaborates with FKTP and clinical laboratories. HbA1c checks need to be carried out to maintain blood sugar levels while participating in prolanis activities. This study aims to determine the comparison of HbA1c results before and after taking prolanis. The research method was comparative analytic using 63 RM data from T2DM patients following prolanis who met the inclusion and exclusion criteria using the Wilcoxon test. The research results showed that the average HbA1c value before prolanis was 7.6%, while the average HbA1c value after prolanis was 7.1%. The Wilcoxon test results showed a significant difference between HbA1c before and after prolanis (p=0.029) with significance (α=0.05). From this research, it is hoped that T2DM patients will follow prolanis more regularly to control blood sugar levels by checking HbA1c both before and after taking prolanis in order to prevent uncontrolled HbA1c values ​​and the occurrence of complications that can cause death in NCDs, especially chronic diseases.